O Messianismo na Palestina Judaica: um estudo comparativo a partir dos Evangelhos Sinóticos e dos Manuscritos do Mar Morto (século I A.C. - 70 D.C.) - Dutra, Luciana Fitarelli (2018)
Ancient Judaism and early Christianity were the propellers of various messianic movements that took place in Jewish Palestine in the first and second century BC and in the first century of our era. These movements did not come out of nowhere, quite the contrary, they had their core within a social, political and ideological context that surrounded the Jewish masses of that period. One of the movements that brought most questions, researches and discussions in the Judeo-Christian area was that of Jesus of Nazareth as well as that of the Essene community interpreted through the Dead Sea Scrolls. Thus, in view of the components of correlation between the Messianic interpretations in the Synotic Gospels and in the Dead Sea Scrolls, one observes their insertion within a scenario embodied in Judaism at the end of the Second Temple, these perceptually marked by these popular shakes. Such a conception underscores the inevitability of studying the impact of the Jewish messianic extract on the accounts of the sayings and deeds of Jesus in the Synotic Gospels and the Dead Sea Scrolls. In view of this, the problem we will try to solve in this work will be: what are the Messianic conceptions in the ideals of Jesus of Nazareth? Would there be patterns of redemptive beliefs in common that characterize the movements and concepts of redemption between the manuscripts of the community of the Essenes and the Synotic Gospels? For such resolution, the methodology of bibliographic revision will be used, having as an addition the comparative textual analysis. The most used sources will be the Gospels of Matthew, Mark and Luke of the Holy Bible and the Dead Sea Scrolls, certainly, not ceasing to use research materials, such as books and articles, as a means of research. The objectives of this work will be to carry out a bibliographical review on Jewish Messianism and the Judaeo-Christian historical context, as well as to address its possible influences on the Jewish people, especially the Essene community; also analyze the similarities and differences of the concept of redemption between the Synotic Gospels and the Dead Sea Scrolls. However, this research does not aim to provide a single and inflexible answer regarding the whole spectrum studied here due to the amount of research that has already been done on the subject.